La Protección Jurídica del Non Nato en el Ecuador - Gabriela Valdivieso Ortega; María Luisa Bossano (Ius Humani. Jornal do direito, 2008)
The focus of this paper is the beginning of life. Analyzing the theories expounded on this topic by various authors, the research seeks to define the origin of the human personality. The paper contains a study of the presumptions of law fixing the beginning of life, under Ecuadorian law, with a view to the protection of this fundamental right. Also outlines the various contradictions on this argument found in our body of law.